Human Resource Management Practices on Inclusive Employment for Persons With Disabilities (PWDs) in the Philippines - Dela Cruz, John Michael M. (Future Science / FSH-PH Publications, 2023)
This study described and examined Human Resource Management practices on inclusive employment for Persons With Disabilities (PWDs) among selected Non-Government Organizations in the Philippines. There were 38 randomly selected Non-Government Organizations in the Philippines which participated in the study. Meanwhile, this study utilized descriptive correlational research. Survey-questionnaire and unstructured interviews were used as the main and secondary research tools of the study. Results revealed that Human Resource Management practices in the employment of Persons with Disabilities among selected Non-Government Organizations in the Philippines offered wide employment opportunities for PWDs. They were compensated equally based on the nature and accomplishments of their work. Hence, they were selected and recruited based on their potentials and skills while emphasizing the prevailing policies on inclusivity and equal work opportunities. Thus, NGOs provided efficient training and development programs towards professional development of PWDs as employees. Further, HR officer implemented policies and regulations that maintained and protected the health and safety status of the PWDs. In addition, productivity was seen as the most advantageous aspect of PWDs in the performance of their work while adjustment to workplace became the most disadvantageous aspect encountered by Human Resource Officers to their PWDs employees.